(untitled) (Research, Society and Development, 2020)
In this work, we present the potential of Augusto Boal’s Theater of the Oppressed to promote reflection in a Chemistry Degree course by theatricalizing chauvinism in a fictitious classroom context. Boal built a theater proposal that uses scenic expression to denounce society’s problems. From that, we simulated some oppressions that students of a Chemistry course involving chauvinism could experience. We emphasize oppressions about a way of doing science, of being a scientist, the chauvinism expressed in the speech and the propagation of these traditions of being a Chemistry teacher. The experience with the Theater of the Oppressed made it possible to act dramatically towards the political positioning of students, the search for democratic institutional instances in their courses and the reflection around the continuing education of higher education teachers. With this, we consider necessary the Chemistry teachers’ education committed to a political, aesthetic and ethical education that takes into account the subjectivities and contexts in the educational process.